Research‐ and health‐related youth advisory groups in Canada: An environmental scan with stakeholder interviews. (19th July 2021) - Chan, Michelle; Scott, Shannon D.; Campbell, Alyson; Elliott, Sarah A.; Brooks, Hannah; Hartling, Lisa
Abstract: Background: Engaging youth throughout the research process improves research quality and outcomes. Youth advisory groups provide one way for youth to express their opinions on relevant issues. Objective: This study aimed to identify research‐ and health‐related youth advisory groups ('groups') in Canada and understand the best practices of these groups. Methods: Google searches and supplementary methods were used to identify relevant groups in Canada. Group information was extracted from websites or through interviews with key informants. Results: We identified 40 groups. Groups were commonly part of a hospital/healthcare facility, nonprofit/health organization or research group. The majority focused on a specific content area, most commonly, mental health. Over half the groups advised on health services. Members' ages ranged from 9 to 35 years. The number of members ranged from 5 to 130. Interviews ( n  = 12) identified seven categories relating to group practices: (a) group purpose/objectives, (b) group development, (c) group operations, (d) group structure, (e) adult involvement, (f) membership and recruitment and (g) group access. Challenges and facilitators to the success of groups were described within the following themes: (a) retaining engagement, (b) creating a safe environment and (c) putting youth in positions of influence. Advice and recommendations were provided regarding the development of a new group. Conclusion: This study provides a comprehensive overview of research‐ and health‐related youth advisory groups in Canada. This information can be used to identify groups that stakeholders could access as well as inform the development of a new group. Patient or Public Contribution: Youth advisory group representatives were interviewed as part of the study.